The maiden of Ludmir : a Jewish holy woman and her world - Deutsch, Nathaniel (S. Mark Taper Foundation imprint in Jewish studies., 2003)
Hannah Rochel Verbermacher, a Hasidic holy woman known as the Maiden of Ludmir, was born in early-nineteenth-century Russia and became famous as the only woman in the three-hundred-year history of Hasidism to function as a rebbe--or charismatic leader--in h.